Association of uric acid levels with cardiac syndrome X: A meta-analysis - Zu, Wu; Li, Chen-Chen; Wang, Xin-Yu; Li, Qiu-Shi; Liu, Bing (Frontiers in Physiology, 2022)
Objective: The pathogenesis of elevated uric acid (UA) levels in patients with cardiac syndrome X (CSX) is unclear, and the results presented in recent papers on UA levels in patients with CSX are controversial. Therefore, we conducted a meta- analysis to assess the relationship between UA levels and CSX. Methods: Three databases, including the Web of Science, EMBASE and PubMed, were systematically searched until January 2022. Fixed-effect and random-effects models were used to analyze the relationship between UA levels and CSX. Subgroup analysis and sensitivity analysis were also performed. Results: Six studies involving 406 CSX patients and 267 non-CSX were included. Our results showed a significant relationship between UA levels and CSX, with a pooled SMD of 0.68 (95% CI 0.37 to 1.00; P＜.0001). We also found a close relationship between UA levels and CSX for patients ≥ 55 years old (SMD:0.70, 95% CI: 0.41 to 0.99, P < .00001), for patients＜55 years old (SMD: 0.68, 95% CI: 0.25 to 1.12, P =.002), for women ≥ 60% (SMD: 0.77, 95% CI: 0.33 to 1.14, P =.0004), for women＜60% (SMD: 0.61, 95% CI:0.23 to 0.98, P =.001), for BMI ≥ 28Kg/m2 (SMD :0.61, 95% CI: 0.23 to 0.98, P =.001), for BMI＜28Kg/m2 (SMD:0.75, 95% CI: 0.31 to 1.19, P =.0009), for publication years ≥ 2012 (SMD :0.69, 95% CI: 0.23 to 1.15, P = .003), for publication years＜2012 (SMD:0.73, 95% CI:0.41 to 1.05, P < .00001), and for Turkey (SMD:0.75, 95% CI:0.38 to 1.11, P <.0001). Sensitivity analysis showed that the pooled results remained consistent after removing any one study or converting the random-effects model to fixed-effects model. Conclusions: Our results indicated a strong association between high UA levels and CSX. However, more well-designed studies are needed to investigate whether early treatment of hyperuricemia can reduce the incidence of CSX.